2022
DOI: 10.1186/s12995-021-00328-w
|View full text |Cite
|
Sign up to set email alerts
|

Health risks and mitigation strategies from occupational exposure to wildland fire: a scoping review

Abstract: Objectives Due to accelerating wildland fire activity, there is mounting urgency to understand, prevent, and mitigate the occupational health impacts associated with wildland fire suppression. The objectives of this review of academic and grey literature were to: Identify the impact of occupational exposure to wildland fires on physical, mental, and emotional health; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 103 publications
0
21
0
Order By: Relevance
“…Respiratory protection may benefit from the use of particulate/organic vapor/formaldehyde filter masks. Respiratory symptoms were less common in this group compared to the ones of particulate only or particulate/organic vapor filter masks [48]. These observations were seen in a simulation lab, and it is of major concern how they may be extrapolated in real-life, with the firefighters' resistance to using these kinds of devices being well-known.…”
Section: Final Remarks and Conclusionmentioning
confidence: 67%
See 1 more Smart Citation
“…Respiratory protection may benefit from the use of particulate/organic vapor/formaldehyde filter masks. Respiratory symptoms were less common in this group compared to the ones of particulate only or particulate/organic vapor filter masks [48]. These observations were seen in a simulation lab, and it is of major concern how they may be extrapolated in real-life, with the firefighters' resistance to using these kinds of devices being well-known.…”
Section: Final Remarks and Conclusionmentioning
confidence: 67%
“…A constant preoccupation must be to establish occupational exposure limits specific to wildland fire smoke, as these circumstances tend to become more and more familiar. Mitigation strategies for such exposures were reviewed in a recent paper [48]. Respiratory protection may benefit from the use of particulate/organic vapor/formaldehyde filter masks.…”
Section: Final Remarks and Conclusionmentioning
confidence: 99%
“…We identified two themes common to all research topics: (1) understanding the dynamic risk environment across wildland fire seasons and roles and (2) organisational fit of mitigation strategies. Despite a different risk environment, the health concerns identified by participants in the current study parallel those by structural firefighters,44 although there is considerably less knowledge specific to health outcomes associated with wildland fire exposure and substantial gaps in knowledge on the long-term health impacts 8…”
Section: Discussionmentioning
confidence: 87%
“…Despite a different risk environment, the health concerns identified by participants in the current study parallel those by structural firefighters, 44 although there is considerably less knowledge specific to health outcomes associated with wildland fire exposure and substantial gaps in knowledge on the longterm health impacts. 8 The most important research topic identified by participants was related to smoke exposure and respiratory health, with 89% of participants indicating it was extremely or very important. During interviews, participants focused on the need for a better understanding of the exposures and health risks associated with wildland fire smoke and the desire for feasible, effective personal protective equipment to protect against smoke inhalation.…”
Section: Areas Of Focus (Subcategory) Examples Of Meaning Unit (Quotes)mentioning
confidence: 99%
See 1 more Smart Citation